Silent witnesses - micro-historical perspectives on suicide in the court records of the first half of the 20th century - Remec, Meta (Prispevki za novejšo zgodovino, 2024)
Based on the archival materials from the Celje and Maribor District Courts (Kreisgerichte) and the specific cases from the Trbovlje County Court (Bezirksgericht), referring to the areas with the highest suicide rates in the Drava Banate, this article examines suicide in the first half of the 20th century. Based on individual cases from judicial practice, as well as newspaper reports, the article sheds light on the social, economic and regional conditions in the considered areas in the first half of the 20th century, as well as the position of women in society and the prevalence of family and sexual violence. At the time when the increasing suicide rates were attributed to the aftermath of World War I, the effects of the economic crisis, and alcoholism, the article analyses the presence and gradual dominance of psychological and psychiatric discourse in determining the causes of individual suicides. By analysing the individual cases, the author presents the attitude towards suicide in rural areas – the shame and stigma still felt by the family members when a relative of theirs commits suicide. The author analyses cases where either the suicide could not be identified or when the corps of the deceased was not found, as well as cases of suicide due to fear and/or shame due to crimes committed. Furthermore, the article focuses on the phenomenon of female suicide and, in this context, on the examples of murder-suicide and the role of women in them, analyses the contemporaneous media discourse, and describes the course of the investigations in the cases where it was not clear whether the death had resulted from suicide or murder.
Keywords: court files; Drava Banate; Dravska banovina; female suicide; microhistory; mikrozgodovina; murder-suicide; samomor žensk; samomori; social history; socialna zgodovina; sodni spisi; suicide; umor-samomor